Effect of Grape Seed Extracts on the Melanosis and Quality of Pacific White Shrimp (Litopenaeus vannamei) during Iced Storage - Sun, Haiyan; Lv, Hua; Yuan, Gaofeng; Fang, Xubo (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2014)
The aim of this study was to investigate the effect of grape seed extracts (GSE) at different concentrations (0, 7.5 and 15 g/L) on the melanosis formation and quality of Pacific white shrimp during 9 days of iced storage. The melanosis formation was significantly inhibited and sensory quality was significantly improved in shrimp treated by various concentration of GSE, compared with the control. The increase of pH, total volatile basic nitrogen content and the total bacteria amounts of shrimp treated by 7.5 and 15 g/L of GSE was significantly retarded. However, the melanosis score, total volatile basic nitrogen, and pH values of shrimp treated by 15 g/L of GSE was lower than that treated by 7.5 g/L of GSE. These results suggested that GSE could be used as an effective natural alternative to synthetic antimelanosic agents to inhibit postmortem melanosis and improve the quality of shrimp during iced storage.